Effect Differences Depth on Chlorophyll Content (Kappaphycus alvarezii) Seaweed Tissue Culture Cultivated in The Waters of Gerupuk Bay - Safitri, Iin; Lumbessy, Salnida Yuniarti; Cokrowati, Nunik (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Seaweed developed through tissue culture techniques has several advantages, such as high carrageenan content, rapid growth, and resistance to disease. In seaweed cultivation, growth is influenced by photosynthetic pigments such as chlorophyll. Chlorophyll plays an important role in converting sunlight into chemical energy needed for growth. This study aims to analyze the chlorophyll content in Kappaphycus alvarezii cultivated at different depths in Gerupuk Bay waters. This study used an experimental method with a completely randomized design (CRD) consisting of 4 treatments and 3 replications, namely depths of 0 cm (P1), 5 cm (P2), 10 cm (P3), and 15 cm (P4). Results of this study indicate that planting at different depths can increase the absolute weight of K. alvarezii tissue culture ranging from 283 g to 356 g, specific growth rate between 5.72%/day to 5.91%/day, seaweed production ranging from 661 g/m2 to 832 g/m2, chlorophyll content between 5.60 mg/L to 21.89 mg/L, and phycoerythrin content between 0.027 mg/L to 0.19 mg/L. The conclusion is that the cultivation of K. alvarezii tissue culture with floating rafts at different depths can affect growth and yield. Cultivation of K. alvarezii seaweed at a depth of 0 cm using the floating raft method gave the best results, namely increasing absolute weight up to 356 g, specific growth rate up to 5.91%/day, and production up to 832 g/m2, supported by chlorophyll content of 21.89 mg/L and phycoerythrin content of 0.195 mg/L. For optimal production results, it is recommended to use a depth of 0 cm in floating raft seaweed cultivation.